Population based epidemiology of ankle sprains attending accident and emergency units in the West Midlands of England, and a survey of UK practice for severe ankle sprains. Issue 6 (17th November 2003) - Bridgman, S A; Clement, D; Downing, A; Walley, G; Phair, I; Maffulli, N
Abstract : Objectives: To estimate the incidence of ankle sprains and severe ankle sprains attending accident and emergency (A&E) units; to describe current practice for severe ankle sprains in A&E units in the United Kingdom. Methods: Crude age and sex specific incidence rates were calculated for four health districts from cases ascertained from data on seven A&E clinical information systems. Case records of patients with ankle sprains at an A&E unit in another health district were audited and the proportion of severe ankle sprains calculated. UK A&E units were surveyed about their usual treatment of patients with severe ankle sprains. Results: The estimate of the crude incidence rate of ankle sprains was a minimum of 52.7 per 10 000, rising to 60.9 (95% CI 59.4 to 62.4) when figures were adjusted for the proportion of patients without a diagnostic code (13.7%). There were important age-sex differences with unadjusted rates observed from 127.8 per 10 000 (CI 115.5 to 140.0) in girls aged 10–14 years to 8.2 (CI 4.2 to 12.3) in men aged 70–74 years. As 14% of ankle sprains attending A&E were classed as severe, this would equate to 42 000 severe ankle sprains per year in the UK. In the UK wide survey, there was a response rate of 79% (211 of 266). Among the responders, Tubigrip was used routinely in 55%, below knee casts in 3%, and braces in 2%. Boots were not used routinely in any unit. Conclusion: While there is considerable variation in severe ankle sprain management in UK A&E units, most are treated with the minimal mechanical support of Tubigrip.